THAILAND ROAD BRIDGE: IMPACT OF MARINE TRAFFIC IN STRAITS OF MALACCA - KAMARUDIN, MUHAMMAD SYAFIQ IZWAN (Journal of Maritime Logistics, 2024)
This research investigates the potential impacts of the Thailand Land Bridge on marine traffic patterns, specifically examining shifts in shipping routes and volumes through the Straits of Malacca (SOM) and identifying the specific types and sizes of vessels most likely to be affected. Through qualitative analysis of interviews with three maritime professionals, the study finds that the Thailand Land Bridge will significantly reduce container traffic through the SOM due to operational efficiencies and cost savings. Large container ships, particularly those carrying high-value and time-sensitive goods will benefit from the shorter, more direct route. Conversely, bulk carriers and tankers are expected to see minimal changes as they rely on specialised port facilities on traditional sea routes. Future research should expand the sample size, incorporate quantitative analysis, and explore environmental and long-term impacts to provide a more comprehensive understanding of the Thailand Land Bridge’s implications for regional maritime logistics.